The Impact of Stress Within and Across Generations: Neuroscientific and Epigenetic Considerations. Issue 4 (July 2021) - Miller, Christopher W. T.
Abstract : Abstract: The impact of stress and trauma on biological systems in humans can be substantial. They can result in epigenetic changes, accelerated brain development and sexual maturation, and predisposition to psychopathology. Such modifications may be accompanied by behavioral, emotional, and cognitive overtones during one's lifetime. Exposure during sensitive periods of neural development may lead to long-lasting effects that may not be affected by subsequent environmental interventions. The cumulative effects of life stressors in an individual may affect offspring's methylome makeup and epigenetic clocks, neurohormonal modulation and stress reactivity, and physiological and reproductive development. While offspring may suffer deleterious effects from parental stress and their own early-life adversity, these factors may also confer traits that prove beneficial and enhance fitness to their own environment. This article synthesizes the data on how stress shapes biological and behavioral dimensions, drawing from preclinical and human models. Advances in this field of knowledge should potentially allow for an improved understanding of how interventions may be increasingly tailored according to individual biomarkers and developmental history.